2018
DOI: 10.1073/pnas.1715998115
|View full text |Cite
|
Sign up to set email alerts
|

hMENA is a key regulator in endothelin-1/β-arrestin1–induced invadopodial function and metastatic process

Abstract: SignificanceDiscovering new targets and novel determinants of metastatic spread is an unmet need in ovarian cancer, which is plagued by high rates of recurrence. Endothelin-1 receptors (ET-1R), belonging to the G-protein–coupled receptor family, represent important targets critically involved in malignant progression. Here we identify a mechanistic link between ET-1R and the actin regulatory protein hMENA/hMENAΔv6 through the specific interaction with the multifunctional protein β-arrestin1 (β-arr1), which ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 38 publications
(67 reference statements)
2
40
0
Order By: Relevance
“…In pancreatic cancer cells, expression of hMENAΔv6, along with a lack of hMENA 11a , is crucial for SMAD2-mediated-TGFβ signaling and invasiveness [ 11 ]. In ovarian cancer, we have recently described an essential function of hMENA/hMENAΔv6 for endothelin1/β-arrestin1-induced invadopodial activity and cancer progression [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In pancreatic cancer cells, expression of hMENAΔv6, along with a lack of hMENA 11a , is crucial for SMAD2-mediated-TGFβ signaling and invasiveness [ 11 ]. In ovarian cancer, we have recently described an essential function of hMENA/hMENAΔv6 for endothelin1/β-arrestin1-induced invadopodial activity and cancer progression [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, β-arrestins regulate specific cellular functions as a result of interacting with defined partner proteins. In PNAS, Di Modugno et al (9) identify hMENA, an actin binding protein of the ENA/VASP family, as a novel interacting partner of β-arr1 critical for endothelin-1 (ET-1) and its cognate receptor ET 1A R signaling in ovarian cancer cell invasion and metastasis ( Fig. 1).…”
mentioning
confidence: 99%
“…Nonetheless, only minimal improvement in the mortality has been observed over the past decade, pointing to the molecular complexity of ovarian cancer and resultant obstacles in developing effective therapies (11). Di Modugno et al (9) used complementary strategies of gene overexpression and knockdown, together with pharmacologic activators and inhibitors, to credibly implicate ET 1A R, β-arr1, and hMENA as mediators of HGSC invasion and metastasis. To implicate ET 1A R, the authors used macitentan, a dual ET 1A R/ET 1B R ligand antagonist, and showed that treatment with macitentan obliterated the ET-1-induced expression of hMENA and proinvasive isoform hMENAΔv6, but decreased expression of the antiinvasive hMENA 11a isoform.…”
mentioning
confidence: 99%
See 2 more Smart Citations